Face Recognition - Mislav Grgic; Kresimir Delac (IntechOpen, 2007)
This book will serve as a handbook for students, researchers and practitioners in the area of automatic (computer) face recognition and inspire some future research ideas by identifying potential research directions. The book consists of 28 chapters, each focusing on a certain aspect of the problem. Within every chapter the reader will be given an overview of background information on the subject at hand and in many cases a description of the authors' original proposed solution. The chapters in this book are sorted alphabetically, according to the first author's surname. They should give the reader a general idea where the current research efforts are heading, both within the face recognition area itself and in interdisciplinary approaches.
English
Keywords: Physical Sciences; Engineering and Technology; Computer and Information Science; Human-Computer Interaction; Security System